Les non musulmans à Istanbul aujourd’hui : une présence en creux ? Le cas de l’arrondissement de Fatih - Jean-François Pérouse (Revue des Mondes Musulmans et de la Méditerranée)
The district of Fatih, located in the heart of the Istanbul historic peninsula could be considered as one of the most characteristic cases when focusing on the place of non-Muslims in present urban space. In fact, we face there with a huge gap between, on one side, the rich and still visible heritages, in terms of architectural traces and of religious buildings – in spite of all the demolitions occurred during the last century – and, on the other side, the now insignificant demographic reality of non-Muslims. In addition, this district’s example shows how local authorities tend to consider more positively the cultural plurality of Istanbul population.